Considerations of Demand-patiern and Economic Return on forest Management and Rationalisaton of Pricing of Timber (teak) - Ashutosh, S.; Chand, Suresh; Pant, N. C.; Sharma, Rajesh (Indian Forester, 1994)
Investments in forestry plantations are long term investment. In such ventures/projects the tree growth is limited by the natural factors, whereas growth of money is governed by numerous market forces. For optimal returns form forestry plantations,it is necessary to follow a management scheme/plan which is evolved after considering the implications of demand-pattent, rate of tree growth and economic retun in terms of sustainable utilization. For sound economic sustainability, it is also essential that there exists a rational basis for pricing of the final product i.e., timber. In this paper an attempt has been made to study and analyse the above concept by taking an example of a teak plantation and using the figures as observed in the Timber Market Survey conducted at Jabalpur.